Penanganan pada Pasien IDCM yang Mengalami Hiperkalemia Berat: Case Report - Saparingga Dasti Putri; Natalia Tambunan; Inggried Angelica Valentina Wiliyams Pen; Sultan Muhammad Wahyu Pamungkas; Ayu Prawesti Priambodo; Ristina Mirwanti (MAHESA : Malahayati Health Student Journal, 2026)
ABSTRACT Idiopathic Dilated Cardiomyopathy (IDCM) is a condition that can trigger malignant arrhythmias such as Ventricular Tachycardia (VT) and Ventricular Fibrillation (VF), especially if accompanied by severe hyperkalemia. The combination of myocardial dysfunction, impaired renal function, and electrolyte imbalance increases the risk of fatal complications such as cardiac arrest. Objective: To report the case management of an IDCM patient with severe hyperkalemia causing malignant arrhythmias, and to highlight the importance of a multidisciplinary approach in its clinical management. This case study uses a single case approach to a 52-year-old patient treated in the Intensive Care Unit. Data were collected through direct assessment, observation, and supporting examinations during five days of intensive care. The patient experienced severe hyperkalemia (K+ 7.05 mmol/L) which triggered VT and progressed to VF. Emergency management was carried out with ACLS, administration of calcium gluconate, insulin-dextrose, Kalitake, sodium bicarbonate, and inotropic support. Hemodialysis was performed to treat persistent electrolyte disturbances. The patient showed significant clinical improvement after comprehensive intervention. Management of severe hyperkalemia in IDCM patients requires coordination between cardiology, nephrology, and intensive care specialists. Rapid intervention, aggressive medical therapy, and hemodialysis can save lives and restore patient stability. Keywords: Nursing Care, Idiopathic Dilated Cardiomyopathy (IDCM), Hyperkalemia.  ABSTRAK Idiopathic Dilated Cardiomyopathy (IDCM) merupakan kondisi yang dapat memicu aritmia maligna seperti Ventricular Tachycardia (VT) dan Ventricular Fibrillation (VF), terutama jika disertai dengan hiperkalemia berat. Kombinasi antara disfungsi miokard, gangguan fungsi ginjal, dan ketidakseimbangan elektrolit memperbesar risiko komplikasi fatal seperti cardiac arrest.Tujuan: Melaporkan penanganan kasus pasien IDCM dengan hiperkalemia berat yang menyebabkan aritmia maligna, serta menyoroti pentingnya pendekatan multidisiplin dalam manajemen klinisnya.Studi kasus ini menggunakan pendekatan single case terhadap pasien berusia 52 tahun yang dirawat di ICU. Data dikumpulkan melalui pengkajian langsung, observasi, dan pemeriksaan penunjang selama lima hari perawatan intensif. Hasil: Pasien mengalami hiperkalemia berat (K+ 7.05 mmol/L) yang memicu VT dan berkembang menjadi VF. Penanganan darurat dilakukan dengan ACLS, pemberian kalsium glukonat, insulin-dextrose, Kalitake, natrium bikarbonat, dan dukungan inotropik. Hemodialisis dilakukan untuk mengatasi gangguan elektrolit yang persisten. Pasien menunjukkan perbaikan klinis signifikan setelah intervensi komprehensif. Penanganan hiperkalemia berat pada pasien IDCM membutuhkan koordinasi antara spesialis kardiologi, nefrologi, dan perawatan intensif. Intervensi cepat, terapi medis agresif, serta hemodialisis dapat menyelamatkan nyawa dan memulihkan stabilitas pasien. Kata Kunci: Asuhan Keperawatan, Idiopathic Dilated Cardiomyopathy (IDCM), Hiperkalemia.